Hierarchical aluminum fumarate metal-organic framework - alumina host matrix: Design and application to CaCl2 composites for thermochemical heat storage. (June 2022) - Touloumet, Quentin; Postole, Georgeta; Silvester, Lishil; Bois, Laurence; Auroux, Aline
Abstract: Aluminum fumarate – porous alumina (AF/Al), synthesized by reactive seeding method, has been used for the first time as a host matrix for CaCl2 -based composite sorbents (CSPM) for thermochemical heat storage (TCHS) applications. The porous matrix and composites containing varying amounts of CaCl2 (20–60 wt%) were fully characterized by combining multiple techniques (N2 adsorption/desorption isotherms, powder X-ray diffraction, scanning electron microscopy, elemental analysis). The storage performances of the studied materials have been investigated using thermogravimetry coupled to differential scanning calorimetry (TG/DSC) and a humidity generator. The results show that the hierarchical porous structure of AF/Al impacts the physico-chemical characteristics, water and heat storage performances and water sorption kinetics. The properties of AF/Al, presenting both micro and mesoporosity, as host matrix for CaCl2 have been compared with those of microporous AF and mesoporous Al. It is evidenced that in AF/Al, the presence of micropores arising from the AF membrane enhances the storage capacity of Al by increasing the number of available sorption sites, while the textural mesoporosity of Al offers favorable conditions for water vapor diffusivity, which is crucial for optimal mass and heat transfer. CaCl2 –AF/Al composites exhibit enhanced water and heat storage capacities compared to the matrix alone, their performances increasing with the salt content to attain 1930 kJ kg −1 and 0.68 kg H 2 O kg −1 for 61 wt% of salt. The hydration level at 25 °C and 30%RH did not exceed a maximum of 4.4 n H 2 O /nanhydrous material, limiting deliquescence and leaching of the salt. A comparative study of the impact of host matrix characteristics on CSPM properties highlights the predominant impact of the salt content on the storage capacity, as well as the influence of porosity on the water vapor sorption behavior. Graphical abstract: Unlabelled Image Highlights: Hierarchical porous structure of the host matrix impacts heat and water storage capacities. AF/Al with 61 wt% CaCl2 can charge up to 1938 kJ kg −1 and 0.68 kgH2 O/kg. Amount of deposited salt is the predominant parameter for CSPM heat and water storages. Available porosity plays a significant role in water sorption kinetics. Maximum hydration level up to 4.4 n H 2 O /nanhydrous materials preserves materials stability.